Microporous structures on mineralized collagen mediate osteogenesis by modulating the osteo-immune response of macrophages - Li, Jun; Luo, Xin; Lv, Zhao-Yong; Qiang, Hui-Fen; Hou, Cai-Yao; Liu, Kun; Meng, Chun-Xiu; Zhang, Yu-Jue; Liu, Feng-Zhen; Zhang, Bin (Frontiers in Bioengineering and Biotechnology, 2022)
The role of biomaterial implantations regulated macrophage reactions and promoting regeneration function is very significant in tissue engineering, and regenerative medicine. Furtherly studying the influence of physicochemical characteristics of implanted biomaterials regulated macrophage polarization to promote bone regeneration is a new hot point. The microporous structure of implanted biomaterials is one of essential aspects affecting macrophage polarization. Early research discovered that the microporous structure of many engraftment biomaterials regulated macrophage polarization, but excluded mineralized collagen (MC). To bridge this knowledge gap, we inferred and manufactured MC with varied microporous structures and researched MC with various microporous structures that regulated macrophages reactions and mediated the osteoblast differentiation of mouse calvaria-derived cells (MC3T3-E1). In this study, we found that about 84 μm microporous structures and 70-80% porosity on MC were conducive to the osteogenic differentiation of MC3T3-E1, advising an advantageous bone immunomodulatory effect. These results indicated the microporous structure and the pore size were essential symbols of macrophages, which affected their spreading and cell morphology and modulated inflammatory response, and enhanced the osteoblastic activities. These data will provide a new idea of biological materials inducing bone repair and direct the optimal design of novel immune biomedical materials, development, and rational usage.